2020
DOI: 10.1001/jama.2019.20967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Surgery vs Endoscopy-First Approach on Pain in Patients With Chronic Pancreatitis

Abstract: ; for the Dutch Pancreatitis Study Group IMPORTANCE For patients with painful chronic pancreatitis, surgical treatment is postponed until medical and endoscopic treatment have failed. Observational studies have suggested that earlier surgery could mitigate disease progression, providing better pain control and preserving pancreatic function. OBJECTIVE To determine whether early surgery is more effective than the endoscopy-first approach in terms of clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS The ESCAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
162
0
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(189 citation statements)
references
References 29 publications
1
162
0
21
Order By: Relevance
“…A recently published multicenter RCT showed that early surgery compared with an endoscopy-first approach resulted in lower pain scores when integrated over 18 months. In addition, the total number of interventions was lower in the early surgery group (median, 1 vs 3; P < .001), altough complications, mortality, pancreatic function and quality of life were comparable [50]. However, further research is needed to assess persistence of differences over time and to replicate the study findings.…”
Section: Original Articlementioning
confidence: 89%
“…A recently published multicenter RCT showed that early surgery compared with an endoscopy-first approach resulted in lower pain scores when integrated over 18 months. In addition, the total number of interventions was lower in the early surgery group (median, 1 vs 3; P < .001), altough complications, mortality, pancreatic function and quality of life were comparable [50]. However, further research is needed to assess persistence of differences over time and to replicate the study findings.…”
Section: Original Articlementioning
confidence: 89%
“…Furthermore, obstruction of the pancreatic duct by, for example, stones or an inflammatory mass in the pancreatic head seems to be the maintaining factor with regard to the severe pain of CP patients. 43 The current study certainly harbors also some limitations.…”
Section: Discussionmentioning
confidence: 89%
“…[ 9 , 18 ] Recently, the ESCAPE study results support that early resection within the first months of opioid use, provides better pain relief with fewer interventions than the current step-up approach. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%